2023
DOI: 10.1136/bmjopen-2022-063026
|View full text |Cite
|
Sign up to set email alerts
|

Minimal important change and difference for knee osteoarthritis outcome measurement tools after non-surgical interventions: a systematic review

Abstract: ObjectivesTo systematically review and provide estimates of the minimal important change (MIC) and difference (MID) for outcome tools in people with knee osteoarthritis (OA) after non-surgical interventions.DesignA systematic review.Data sourcesMEDLINE, CINAHL, Web of Science, Scopus and Cochrane databases were searched up to 21 September 2021.Eligibility criteriaWe included studies that calculated MIC and MID using any calculation method including anchor, consensus and distribution methods, for any knee OA ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 93 publications
(268 reference statements)
0
4
0
Order By: Relevance
“…Similar results were observed for the other KOOS scales such as KOOS ADL, with a median of 82.35 and a 75th percentile value of 95.59. At the 9-month follow-up in this study, the relative change of 27.78, 27.94, and 18.75 in median scores of KOOS pain, ADL, and QoL, respectively, were above the highest values of what could be tentatively considered as the minimal clinically important changes in the literature for non-operative treatments [ 16 , 17 ]. The treatment responder rate was calculated at the month 6 follow-up visit according to the OMERACT-OARSI proposed set of responder criteria and was 72.7%.…”
Section: Discussionmentioning
confidence: 59%
“…Similar results were observed for the other KOOS scales such as KOOS ADL, with a median of 82.35 and a 75th percentile value of 95.59. At the 9-month follow-up in this study, the relative change of 27.78, 27.94, and 18.75 in median scores of KOOS pain, ADL, and QoL, respectively, were above the highest values of what could be tentatively considered as the minimal clinically important changes in the literature for non-operative treatments [ 16 , 17 ]. The treatment responder rate was calculated at the month 6 follow-up visit according to the OMERACT-OARSI proposed set of responder criteria and was 72.7%.…”
Section: Discussionmentioning
confidence: 59%
“…We included studies that reported Δ knee flexion as well as Δ pain or Δ function outcomes measured using tools with established MCICs [ 32 ]. The tools included intermittent and constant osteoarthritis pain, Knee injury and Osteoarthritis Outcome Score, Lower Extremity Functional Scale, Numeric Pain Rating Scale, Patient-Reported Outcome Measurement Information System, and 36-Item Short-Form Health Survey, VAS and WOMAC.…”
Section: Methodsmentioning
confidence: 99%
“…This sample size will also be sufficient to detect a minimal important change in KOOS 4 estimated at 10 points in patients with knee OA (with a common between-subject SD of 15). 62 …”
Section: Data Managementmentioning
confidence: 99%